Mechanical, morphological, and tribological behavior of Eulaliopsis binata fiber epoxy composites. Issue 12 (15th October 2020) - Pradhan, Subhrajit; Acharya, Samir Kumar; Prakash, Ved
Abstract: This study is aimed at the potential use of a new natural fiber in polymer based composites ( Eulaliopsis binata fiber) as a reinforcing material whose potential for tribological applications is still an unexposed area of research. The characterization studies of the fiber has been carried out with XRD, EDS, and Scanning electron microscope (SEM). Different weight percentages (10, 20, 30, and 40%) of short fiber were taken as reinforcement with epoxy polymer resin and hardener to study the tensile, flexural, and impact strength as well as the abrasive wear behavior of the developed composites. The experimental results indicate significant improvement in the mechanical and wear properties of epoxy with the incorporation of Eulaliopsis binata (EB) fiber. The composites containing 30 and 20 weight fraction of Eulaliopsis binata fiber exhibit optimum mechanical properties and abrasion resistance, respectively. The fractured and worn surfaces of the composites were studied under SEM to find out the failure mechanisms. Abstract :